Comparison of international protein corporation 740 fish meal and special select™ menhaden fish meal in nursery pig diets - M G Young; M Cici; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2001)
One hundred and seventy five pigs (initially weighing 14.1 lb and 17 + 2 d of age) were used in a 21-d growth assay to compare performance of pigs fed two sources of Menhaden fish meal. Overall, there was no difference in growth performance between the two fish meal sources. For the first 14 days ADG and F/G were improved by including fish meal in the diet and as the level increased from 2.5 to 5%. However, in the third week (day 14 to 21) of the trial there was no benefit in adding fish meal to the diet. These results indicate that IPC 740 fish meal can be an effective replacement for Special Selectâ„¢ Menhaden fish meal in nursery diets.; Swine Day, Manhattan, KS, November 15, 2001
Keywords: Swine day; 2001; Kansas Agricultural Experiment Station contribution; no. 02-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 880; Swine; Starter pigs; Fish meal; Performance